Introducción de demostraciones prácticas para la enseñanza de la física en las aulas universitarias - Vázquez Dorrío, J. B.; García Parada, E.; González Fernández, P. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1994)
An analysis about utility, characteristics and structure of the so called «practical dernonstrations» is presented in order to introduce a dynamic element in the classroom. Although in apparent contradiction with didactic modern trends that proclaim «what students are able to do by themselves, teachers should not do», practical demonstrations should be placed in an active methodological approach as a complement in the exposition of the contents, getting some importance concerning student passivity, lack of didactic facilities and high number of students per classroom.